SUGGESTED CORRECTIONS TO TEXTBOOK ENTITLED: “JURUS SAKTI TAKLUKKAN BAHASA MANDARIN TANPA KURSUS; TANPA GURU” - Pradono, Sudono Noto (Akademi Sekretari Widya Mandala, 2017)
The purpose of this article is to suggest corrections to a published book. The writer has analyzed the book entitled “Jurus Sakti Taklukkan Bahasa Mandarin Tanpa Kursus; Tanpa Perlu Guru” (“Magic Ways to Conquer Mandarin without a Course; no Teacher Required”) by marking the mistakes, and then has classified the mistakes based on 1) phonetics, and 2) characters. The mistakes are discussed and the corrections are suggested. It seems that “you can’t judge a book by its cover” is true. The readers’ first impression is usually the title on the cover of the book, and this first impression could be wrong because the content of the book has many mistakes. If the book does not give a correct model of Mandarin language, how the readers can learn Mandarin language well.